The Effectiveness of Hypnotherapy to Reduce Anxiety in Pre-Caesarean Section Women - Mubarokah, Rizka Innayatun; Prasetya, Hanung; Respati, Supriyadi Hari (Journal of Maternal and Child Health, 2020)
Background: Anxiety felt by women before delivery with cesarean section can cause psycho